A review of game-based learning as a tool to stimulate learning process for autism spectrum disorder (ASD) children / Mohd Iftitah Jamil, Zainuddin Ibrahim and Hawa Najihah Muhamad Basri - Jamil, Mohd Iftitah; Ibrahim, Zainuddin; Muhamad Basri, Hawa Najihah (College of Creative Arts, 2025)
There is a strong emphasis on the use of technology in the delivery of the academic process. It is especially important for students who struggle with the daily learning process, such as children with Autism Spectrum Disorder (ASD). Game-based learning (GBL) is an effective tool for stimulating the learning process in children with ASD. With the increasing prevalence of ASD and the variety of challenges faced by students on the spectrum in traditional educational settings, there is a growing need for innovative approaches to improve their learning experiences. GBL, with its interactive and engaging elements, has the potential to cater to the unique learning styles and preferences of children with ASD. GBL's interactive and adaptive nature meets the cognitive needs of ASD children, resulting in a more inclusive and engaging learning environment. Examining existing studies and interventions that use GBL to stimulate the learning process for children with ASD, shedding light on the positive outcomes observed in terms of engagement, motivation, and skill acquisition. Using information from previous writings, it discovered improvements in communication skills and academic achievement among ASD children who used the GBL technique. Educators can better address the specific learning needs of ASD children by understanding the cognitive processes involved in GBL. This review has the potential to pave the way for future research and improvements in the use of GBL in ASD educational contexts. Finally, this review contributes to a better understanding of how GBL can be used as a valuable tool to stimulate learning in children with ASD. It aims to inform educators and practitioners about the potential benefits of implementing GBL for children with ASD by synthesizing existing knowledge and identifying areas for further research.